(untitled) (Research, Society and Development, 2021)
This study aims to conduct a literature survey about the care of patients with hypertension in primary health care. This is an integrative literature review, the search occurred in the Virtual Health Library (VHL), with the help of the databases Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), Nursing Database (BDENF) and PUBMED. The articles were collected from January to February 2021. The following descriptors were used: Primary health care, Patient care, Hypertension, and Health promotion. After applying the inclusion criteria, 20 studies remained. This study shows that it is necessary the performance of the multidisciplinary team in combating hypertension in primary care, using the strategies protocoled by the Ministry of Health, highlighting health education, which through the actions taken is possible to maintain disease control in hypertensive patients.